Phytochemical Compositions and Antioxidant Properties of Combined Funtumia africana and Abutilon mauritianum Extract (CFAE) - Robert Ikechukwu Uroko; Charles Nnanna Chukwu; Chinomso Friday Aaron; Umezurike Benedict Chidozie; Doris Akachukwu; Ndukwe Onyeani Atuh (Biology, Medicine, & Natural Product Chemistry, 2022)
Medically active compounds in plants confer biological effects including antioxidant properties. This study evaluated the phytochemical content and in vitro antioxidant properties of combined Funtumia africana leaves and Abutilon mauritianum extract (CFAE). The 1,1-diphenyl-2-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP), thiobarbituric acid reactive substances (TBARS), total antioxidant capacity (TAC), and nitric oxide radical (NO.) scavenging capabilities were used as antioxidant assay models. The results of the phytochemical analysis showed that CFAE is rich in alkaloids, flavonoids, tannins, saponins, phenols and cardiac glycosides. The extract contains antioxidant vitamins A, C and E, vitamin E being the most abundant. The CFAE showed a dose-dependent TAC based on the observed FRAP, TBARS, and DPPH scavenging activity which could be attributed to the presence of phenolic compounds and vitamins E. These strongly suggest that CFAE is a potential source of phytochemicals and antioxidants which could be exploited in the food and pharmaceutical industries in production of potent nutraceuticals or therapeutically-important products.